Peter Brook and the Empty Space: A Framework for Playing and Learning - Vieites, Manuel F. (2024)
Introduction: The concept of empty space is one of Peter Brook’s most cited formulations. Along with other related concepts and based on the basic premise of “as if”, he refers to a framework to develop action as, and in play. Objective: Therefore, this paper intends to define this set of concepts, their genealogy in the scenic practice, and their scope in the construction of the action and the development of training processes. Methods: This study is based on a theoretical investigation. It performs an analysis on Brook’s works and a review of literature. Results: Based on the considered concepts, some criteria on the development of social and stage acting learning were established. Conclusions: Some of Brook’s contributions to the development of theatre pedagogy as a science of education were argued.